1997
DOI: 10.1007/s004670050245
|View full text |Cite
|
Sign up to set email alerts
|

Culture of embryonic renal collecting duct epithelia in a gradient container

Abstract: During organogenesis the ampullar epithelium of the renal collecting duct acts as an inducer which generates all of the nephron anlagen. As development proceeds, one part of the collecting duct cells in the ampullar tip retain their inducer capability, while others develop into the functional epithelium consisting of principal and intercalated (IC) cells. The events leading from the embryonic inducer to the mature tissue are unknown. We investigated the maturation of embryonic collecting duct epithelium derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…Under these conditions the tissue receives constant nutrition, harmful metabolic products do not accumulate and paracrine factors remain at a physiological level. Previous experiments have shown that embryonic CD epithelia can be cultured in a container for weeks and months exhibiting a morphology comparable to the situation within the maturing kidney [6, 7, 20]. …”
Section: Prerequisitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions the tissue receives constant nutrition, harmful metabolic products do not accumulate and paracrine factors remain at a physiological level. Previous experiments have shown that embryonic CD epithelia can be cultured in a container for weeks and months exhibiting a morphology comparable to the situation within the maturing kidney [6, 7, 20]. …”
Section: Prerequisitesmentioning
confidence: 99%
“…Tissue culture experiments with embryonic CD epithelia revealed that the development of individual CD cell features can be triggered by aldosterone [19], amiloride [20]and the extracellular electrolyte environment [21, 22]. Under static culture conditions in medium containing serum, aldosterone is known to generate a P cell-like epithelium with an amiloride-sensitive Na + transport and tight characteristics [23].…”
Section: Humoral and Environmental Factors Modulate Differentiationmentioning
confidence: 99%
“…Application of a gradient perfusion culture container made it further possible to investigate the influence on differentiation of different fluid composition at the luminal and basal sides of embryonic renal collecting duct (CD) epithelia (Minuth et al 1992b(Minuth et al , 1997a(Minuth et al , b, 1999(Minuth et al , 2001(Minuth et al , 2005aSteiner et al 1997, Schumacher et al 2002aMinuth et al 2009a). In the course of performed experiments it was detected that development of a CD epithelium starts with an unexpected long latent period of three days and needs at least 10 days for up-regulation of typical signs of differentiation.…”
Section: Featuring Development Of Epitheliamentioning
confidence: 99%
“…1A) were transferred to a gradient perfusion culture container ( fig. 1B; Minucells and Minutissue) to create optimized culture conditions [16]. Fresh medium was continuously superfused on the basal and luminal sides of the epithelia for the following culture period of 13 days at a rate of 1 ml/h with an IPC N8 peristaltic pump (Ismatec, Wertheim, Germany; fig.…”
Section: Gradient Perfusion Culture Of Embryonic CD Epitheliamentioning
confidence: 99%
“…Epithelia cultured in media with a low Na content showed a completely different developmental pattern as compared with epithelia cultured in media with a high Na content. Evidence for a definitive electrolyte-sensitive reaction during CD development was finally obtained by culturing the embryonic epithelia in the presence of aldosterone and under serum-free conditions in a gradient container [16]. During a culture period of 14 days, epithelia cultured with the same medium on luminal and basal sides develop completely different features as compared with epithelia cultured with different media on both sides [8,11].…”
Section: Introductionmentioning
confidence: 99%